2019
DOI: 10.1177/2325967119838251
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Comparison of the Arciero and LaPrade Reconstruction for Posterolateral Corner Knee Injuries

Abstract: Background: Injury to the posterolateral corner (PLC) of the knee requires reconstruction to restore coronal and rotary stability. Two commonly used procedures are the Arciero reconstruction technique (ART) and the LaPrade reconstruction technique (LRT). To the authors’ knowledge, these techniques have not been biomechanically compared against one another. Purpose: To identify if one of these reconstruction techniques better restores stability to a PLC-deficient knee an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…A recent biomechanical study looking at the biomechanics of the Arciero reconstruction technique and the LaPrade reconstruction technique showed that both techniques were equally effective in restoring stability to knees with PLC injuries. 14 The authors recommend, as do we, that surgeons should select a reconstruction technique based on their experience and training to address these injuries. 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent biomechanical study looking at the biomechanics of the Arciero reconstruction technique and the LaPrade reconstruction technique showed that both techniques were equally effective in restoring stability to knees with PLC injuries. 14 The authors recommend, as do we, that surgeons should select a reconstruction technique based on their experience and training to address these injuries. 14 …”
Section: Discussionmentioning
confidence: 99%
“…A recent biomechanical study looking at the biomechanics of the Arciero reconstruction technique and the LaPrade reconstruction technique showed that both techniques were equally effective in restoring stability to knees with PLC injuries. 14 The authors recommend, as do we, that surgeons should select a reconstruction technique based The graft should be tensioned in slight valgus and 30 of flexion Passing sutures can be left in the fibular tunnel after drilling to facilitate graft passage A Cobb elevate can be placed posterior to the fibular head while drilling to prevent common peroneal nerve injury…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,14,21 Ultimately, the top of the research pyramid is our clinical outcome studies, [22][23][24][25][26] which we believe have significantly improved the treatment of injuries to the posterolateral corner to the point at which it is no longer considered the dark side of the knee. 27,28 Other authors have validated our anatomic-based posterolateral knee reconstruction clinically, 29 and Treme et al 30 biomechanically compared this technique with other techniques. Franciozi et al 31 reported a clinical study using a hamstring autograft technique that was very similar to the anatomic-based reconstruction technique presented in the study by Vezeridis et al 1 Overall, we believe that refining anatomic-based reconstruction procedures should be the next research topic to improve posterolateral corner reconstruction.…”
Section: Posterolateral Corner Reconstruction Comparing a Fibular-basmentioning
confidence: 87%
“…PLC reconstructions can be performed using techniques described by LaPrade or Arciero. A recent biomechanical study [46] showed these to be equally effective; however, the Arciero reconstruction requires only a single semitendinosus graft, whereas LaPrade's technique requires an additional gracilis graft. Another option for the PLC is performing a biceps tenodesis.…”
Section: Lateral Collateral Ligament (Lcl) and Plcmentioning
confidence: 99%